2010
DOI: 10.1039/c0jm00441c
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber composite membranes with low equivalent weight perfluorosulfonic acid polymers

Abstract: Two low equivalent weight perfluorosulfonic acid (PFSA) polymers (825 EW and 733 EW) were successfully electrospun into nanofibers by adding as little as 0.3 wt% of high molecular weight poly(ethylene oxide) as a carrier polymer. The electrospun fiber morphology transitioned from cylindrical filaments to flat ribbons as the total concentration of PFSA + carrier in solution increased from 5 wt% to 30 wt%. PFSA nanofiber mats were transformed into defect-free dense membranes using a four-step procedure: (i) anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 15 publications
(19 reference statements)
5
86
1
Order By: Relevance
“…Nah et al [10] reported a three times enhancement of the ionic conductivity as comparing the electrospun Nafion nanofiber membranes with dense films, while Dong's [8] research demonstrated that a further improvement could be achieved up to an order of magnitude higher if high-purity Nafion was employed. Furthermore, Choi et al [11] fabricated nanofiber membranes successfully with PFSA and 0.3 wt.% high molecular weight PEO, and these membranes exhibited higher proton conductivities than that of commercial Nafion 212 membranes. Many of these works, however, only focused on the factors associated with polymer composition in blend solutions such as the type of carrier polymer, polymer concentration as well as the ratio of polymer to PFSA resin.…”
Section: Introductionmentioning
confidence: 94%
“…Nah et al [10] reported a three times enhancement of the ionic conductivity as comparing the electrospun Nafion nanofiber membranes with dense films, while Dong's [8] research demonstrated that a further improvement could be achieved up to an order of magnitude higher if high-purity Nafion was employed. Furthermore, Choi et al [11] fabricated nanofiber membranes successfully with PFSA and 0.3 wt.% high molecular weight PEO, and these membranes exhibited higher proton conductivities than that of commercial Nafion 212 membranes. Many of these works, however, only focused on the factors associated with polymer composition in blend solutions such as the type of carrier polymer, polymer concentration as well as the ratio of polymer to PFSA resin.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, the electrospinning process has attracted wide attentions in fabricating membranes, which fabricates nanofibers with porous morphology and large specific surface area [18][19][20][21]. Through a simple hot-press treatment, the corresponding membranes can be formed and tend to be dense in macroscopic scale but loose in microscopic scale.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun membranes have been widely investigated in several areas, such as lithium secondary batteries, biomedical materials, filters, and clothing to protect against electromagnetic waves, sensors, radioactive radiation, and electronic devices [16e19]. Up to now, however, there have only been a few reports on PEMs based on the electrospinning method [20,21]. Electrospun PEMs with good stability and high performance in high temperature conditions have not yet been reported, to the best of the authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%